2006
DOI: 10.1002/chem.200501326
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Inverted Redox Potentials and Aromaticity in the Oxidized States of New π‐Electron Donors: 9‐(1,3‐Dithiol‐2‐ylidene)fluorene and 9‐(1,3‐Dithiol‐2‐ylidene)thioxanthene Derivatives

Abstract: Derivatives of 9-(1,3-dithiol-2-ylidene)fluorene (9) and 9-(1,3-dithiol-2-ylidene)thioxanthene (10) have been synthesised using Horner-Wadsworth-Emmons reactions of (1,3-dithiol-2-yl)phosphonate reagents with fluorenone and thioxanthen-9-one. X-ray crystallography, solution electrochemistry, optical spectroscopy, spectroelectrochemistry and simultaneous electrochemistry and electron paramagnetic resonance (SEEPR), combined with theoretical calculations performed at the B3P86/6-31G** level, elucidate the interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…We have previously observed a large variation in the thermodynamic stability of radical anions of fluorene-based acceptor molecules [14] as well as of radical cations of 1,3-dithiole-based donor molecules. [35] In the most extreme case, the radical cation of a p-extended dithiole derivative is completely destabilised, which gives rise to a truly two-electron (inverted potentials) oxidation process. [35,36] In dithiole-fluorene diads, a complete coalescence of the first and second reduction waves has never been observed, although the thermodynamic stability of species AC À has a slight tendency to decrease with a reduction in the electronwithdrawing character of substituents in the fluorene moiety (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously observed a large variation in the thermodynamic stability of radical anions of fluorene-based acceptor molecules [14] as well as of radical cations of 1,3-dithiole-based donor molecules. [35] In the most extreme case, the radical cation of a p-extended dithiole derivative is completely destabilised, which gives rise to a truly two-electron (inverted potentials) oxidation process. [35,36] In dithiole-fluorene diads, a complete coalescence of the first and second reduction waves has never been observed, although the thermodynamic stability of species AC À has a slight tendency to decrease with a reduction in the electronwithdrawing character of substituents in the fluorene moiety (cf.…”
Section: Resultsmentioning
confidence: 99%
“…The C9 À C14 bond, which must be a single bond in 1 b, is indeed longer in compounds 7 to 13 than in 14 (1.367(3) ) in which the fluorene moiety has little electron-withdrawing ability [35] (see Table 4). The lengthening (as well as the twist around this bond) is stronger when the dithiole moiety carries electron-releasing substituents (7 a, 8 a) and weaker when it has electron-withdrawing CO 2 Me substituents (10 a, 11 a), although the effect only marginally exceeds experimental error, and the C15= C16 bond distance (which must lengthen with the increase in ICT) is even less sensitive.…”
mentioning
confidence: 99%
“…Pristine truxene and 9-(1,3-dithiol-2-ylidene)fluorene [15] (4; see Figure 2) were studied as reference systems. The minimumenergy conformation calculated for 3 a corresponds to a C 3 -symmetric structure with the symmetry axis passing through the center of the inner benzene ring (see Figure S1 in the Supporting Information).…”
mentioning
confidence: 99%
“…(Figure 6). Ligand L4Pyr exhibits one reversible oxidation wave at E1 ox = 0.57 V vs. Fc/Fc + which is attributed to the formation of the DTF radical-cation [27,28]. This potential is higher by 0.15 V compared to the one of the homologous ligand bearing two pyridine-3-yl units [29].…”
Section: Resultsmentioning
confidence: 96%
“…In the course of our research related to the preparation of electron-rich self-assemblies [17,[19][20][21][22][23][24][25][26], we have recently demonstrated that the 9-(1,3-dithiol-2-ylidene)fluorene moiety, which is known to be readily and reversibly oxidized into a cation-radical [27,28], can be used as a building-block for the construction of electro-active self-assembled cages [29]. In line with this work, we describe herein the synthesis of an original electron-rich M 2 L 2 metalla-macrocycle constructed from the cis-blocked Pd(dppf)OTf 2 Pd(dppf)OTf2 (dppf = 1,1′-Bis(diphenylphosphino)ferrocene) acceptor and a 9-(1,3-dithiol-2-ylidene)fluorene ligand (L4Pyr) that incorporates two pyridin-4-yl units in the corresponding 3,6-positions.…”
Section: Introductionmentioning
confidence: 99%